The use of bone age in clinical practice - part 1 - Martin, David Dominique; Wit, Jan M.; Hochberg, Ze’ev; Sävendahl, Lars; Rijn, Rick R. van; Fricke, Oliver; Cameron, Noël; Caliebe, Janina; Hertel, Thomas; Choukair, Daniela; Albertsson-Wikland, Kerstin; Thodberg, Hans Henrik; et al. (Hormone research in paediatrics, 2011)
This review examines the role of skeletal maturity (‘bone age’, BA) assessment in clinical practice. BA is mainly used in children with the following conditions: short stature (addressed in part 1 of this review), tall stature, early or late puberty, and congenital adrenal hyperplasia (all addressed in part 2). Various manual and automatic methods of BA assessment have been developed. Healthy tall children tend to have advanced BA and healthy short children tend to have delayed BA in comparison to chronological age. Growth hormone (GH) treatment of children with GH deficiency leads to a catch-up in BA that is usually appropriate for the height of the child. Response to GH is dependent on BA delay in young children with idiopathic short stature, and GH dosage appears to affect BA acceleration. In chronic renal failure, BA is delayed until puberty but then increases due to increased sensitivity of the growth plate to sex steroids, thus further impairing adult height. The assessment of BA provides an important contribution to the diagnostic workup and management of children with short stature.
Gesehen am 11.08.2022